Efisiensi Penggunaan Dosis Optimum Poly Aluminium Chloride (PAC) Terhadap Volume Lumpur yang Terkandung dalam Satu Liter Air Baku - Putri Cahyaning Sri Hartini; Munawar Ali (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Sludge is a by-product of an activity that comes from the discharge outlet of the flocculation, sedimentation and backwash filtration basins. To determine the volume of sludge contained in one liter of raw water, it is necessary to conduct a Jartest Test by determining the optimum dose of PAC. This water sampling was carried out at the Krian 1 Water Treatment Plant (IPA). Primary data collection is obtained from Imhoff Cone Results data. While for secondary data collection we get from Jartest data. The manufacture of the coagulant solution used is Poly Aluminum Chloride (PAC). The average turbidity value in February was around 123 NTU and there was an increase in turbidity on the seventh day which reached 237 NTU. The drastic increase in turbidity reached 455 NTU with an average turbidity in March of 130 NTU. The graph shows that there is a significant correlation between the volume of sludge produced during the treatment process and the level of water turbidity. Thus, the researcher suggests further treatment of the remaining sludge which can be done by making a Sludge Drying Bed (SDB).